Carbon credits, the tree that hides the forest? - Tin Fischer (The UNESCO Courier, 2023)
The worth of a felled tree is easy to quantify; currently, lumber is worth about US350. But what is the value of a standing tree? It is obviously valuable for biodiversity, for the climate, for humans and agriculture: a forest provides habitat for birds, stores carbon, casts shadow and regulates rainfall. But these are not financial values, therefore leaving forests vulnerable for clearance. So a new idea emerged.